The Socio-Economic Effects of Human Trafficking in Nigeria - Goddy Uwa, Osimen; Okor, Pedro; Osayin, Daudu, Basil; Tolulope Abayomi, Adeniran, (IJRDO - Journal of Social Science and Humanities Research, 2018)
Human trafficking is globally recognised as modern day slavery with multifarious negative socio-economic, legal and health implications. Besides drug trafficking and gun running, human trafficking has become a lucrative business globally and yields an estimate of US $32 million annually. Traffickers trade on human lives; subject them to gory and traumatic experiences in order to make profits. Human trafficking is therefore the worst form of human right violations and gender based violence against female who constitute majority of the victims in the country. Regrettably, Nigeria occupies the ignoble position of a source, transit and destination country for trafficking in the recent times, the scourge has assumed complex dimensions, become more elusive, shrouded in secrecy and with the attendant consequences and implication on the lives in the country. Data from the National Agency for the Prohibition of Traffic in Persons (NAPTIP) shows that seventy eight percent of victims of human trafficking in Nigeria fall within the age range of 8 – 27 years, children within this age bracket are naturally of school going age.  Victims of trafficking miss educational opportunities needed for today’s globalised world. This paper was based on the dynamics of human trafficking in Nigeria, some emerging trends in trafficking, the socio-economic implications, government’s strategies in curbing the menace and possible adoption as good practice.